Regulasi dan Perlindungan Konsumen dalam Ekosistem Fintech Syariah: Posisi Aggregator sebagai Perantara Informasi Produk Keuangan - Mulyana, Iwan; Sulanjana, Rukanda Ahmad (STAI Al Musaddadiyah Garut, 2025)
The rapid development of financial technology (fintech) has given rise to new business models, one of which is the aggregator, which functions as an intermediary for financial product information. The presence of aggregators facilitates consumers in comparing various financial products; however, it also poses new challenges related to information transparency, consumer protection, and compliance with Sharia principles, particularly in Islamic financial products. This study aims to analyze the legal position of aggregators, examine regulatory obligations concerning transparency and consumer protection, and compare governance practices in the marketing of Islamic financial products involving aggregators. The research employs a literature review and policy analysis of relevant laws, regulations, and related documents. The findings indicate that Financial Services Authority Regulation (POJK) Number 4 of 2025 has provided a normative foundation for the regulation of aggregators; nevertheless, its implementation still leaves gaps, especially in the standardization of Sharia compliance information disclosure. The comparative analysis also reveals differences in orientation between conventional aggregators and Sharia-specific aggregators. This study recommends strengthening standard clauses on aggregator platforms, including clarity of contracts, fee transparency, and structured complaint-handling mechanisms, in order to enhance consumer protection and ensure Sharia compliance. Keywords: financial aggregators; consumer protection; Islamic finance; fintech regulation; information transparency.